Model use in sustainability policy making: An experimental study. (December 2017) - Czaika, Ellen; Selin, Noelle E.
Abstract: We examine whether decision makers who use a system dynamics model more readily create policies whose outcomes match their stated priorities or are on the Pareto Frontier of achieved outcomes, and whether model users are more likely to change their priorities. Comparing model use with other decision tools, we address these questions in a role-play simulation (serious game) experiment in which participants make multi-dimensional policy recommendations to address environmental, economic, and social equity dimensions of sustainability. Participants are randomly assigned to use one of four decision support tools: (1) actively using the model or passively being briefed. The briefings cover: (2) the insights of the model; (3) general, relevant information; or (4) irrelevant information (control). We find that model-users, group (1), discovered key insights about win-win opportunities—over-performing their priorities—and most readily created policies on the Pareto Frontier of achieved outcomes. Groups (2) and (3) best matched their policy outcomes to their priorities, missing the win-win. Highlights: Experimental study comparing model use with use of other decision support tools a busy policy maker might employ. 73% of model users found a win-win in the policy trade space; only 7%, 13%, and 0% of users of the other DISTs did. Model users most readily, of the experimental categories, created policies on the Pareto Frontier of achieved outcomes. Decision makers who heard relevant presentations readily created policies that matched their stated priorities.